Pengaruh Produk Domestik Regional Bruto, Upah dan Inflasi Terhadap Pengangguran di Kabupaten/Kota Provinsi Kalimantan Selatan - Masdarika Masdarika; Muhammad Effendi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to see how the variables of gross domestic, regional product, wage, and inflation influence unemployment in regencies/cities in South Kalimantan and which factor has the most dominant influence on unemployment itself. This study uses secondary data from 2014-2019; the research area includes 13 districts/cities in South Kalimantan. This study uses cross-section data and time-series data, so the data analysis technique is multiple linear regression analysis with fixed effect model estimates. Multiple linear regression analysis of panel data shows that the gross regional domestic product variable has a significant and positive effect on unemployment. In contrast, other variables, namely wages and inflation, have a negative and insignificant impact on unemployment in the Regency / City of South Kalimantan Province.